Evaluasi Kebijakan Pemerintahan Tentang Perlindungan Hutan Di Kabupaten Bengkalis - Herdasuri, Reza; Syafhendry, Syafhendry (UIR PRESS, 2015)
The background for this study is the amount of damage that occurs in mangrove forests caused either due to natural factors and human factors. Visible phenomena is the number of illegal logging occurs either by the public or for commercial purposes, the amount of diversion function of mangrove forests into housing estates, roads and farms and the lack of rehabilitation of mangrove forests. In this study the authors used a method of quantitative and qualitative means to conduct an analysis of the implementation of Government Regulation No. 45 Year 2004 on Forest Protection, which was then elaborated based on information obtained through questionnaires distributed to respondents, and the result of in-depth interviews as well as data that are already in form documents. From the results of the evaluation conducted by the author with taking 66 respondents consisting of representatives from governments and communities, it can be concluded that the implementation of government policies on the protection of forests in Bengkalis less well because of the lack of effort made by the Local Government Bengkalis to prevent logging illegal both by society and by certain parties for commercial purposes, precautions occurrence pengalihfungsian land mangrove carried out by the Local Government Bengkalis still not good, either for the plantations, residential as well as for the manufacture of shrimp farms, still lack the process of rehabilitation mangrove whether conducted by the Local Government Bengkalis and by society, and even the rehabilitation process is mostly done by people on their own initiative as well as the lack of implementation of strict punishment of the Local Government Bengkalis for violations of the law in order to safeguard and protect the health of the mangrove forest